2021
DOI: 10.1038/s41598-021-90955-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in each retinal layer and ellipsoid zone recovery after full-thickness macular hole surgery

Abstract: To analyze the changes in each retinal layer and the recovery of the ellipsoid zone (EZ) after full-thickness macular hole (FTMH) surgery. Patients who underwent surgery for FTMH were included. Spectral-domain optical coherence tomography (SD-OCT) was performed preoperatively and postoperatively at 1, 3, 6, 9, and 12 months. A total of 32 eyes were enrolled. Ganglion cell layer, inner plexiform layer, and inner nuclear layer showed significant reductions over time after surgery (P = 0.020, P = 0.001, and P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…BCVA was significantly correlated with axial length and DHI at baseline. Lee et al found that long axial length may impair EZ recovery, resulting in poorer functional visual outcomes (22), which is consistent with our finding of a negative correlation between axial length and BCVA. As no single EZ-related preoperative parameter differed significantly between groups A and B, a larger sample size and measurement of other OCT parameters related to the EZ band are needed in future research investigating the close relationship between the EZ band and photoreceptor function.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…BCVA was significantly correlated with axial length and DHI at baseline. Lee et al found that long axial length may impair EZ recovery, resulting in poorer functional visual outcomes (22), which is consistent with our finding of a negative correlation between axial length and BCVA. As no single EZ-related preoperative parameter differed significantly between groups A and B, a larger sample size and measurement of other OCT parameters related to the EZ band are needed in future research investigating the close relationship between the EZ band and photoreceptor function.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that the ratio of closed EZ band in Group A was significantly higher than in Group B at 1- and 6-months postoperative visits, showing a positive correlation between EZ band recovery and BCVA, which is consistent with previous studies. In terms of thickness, Lee et al found that BCVA was affected by inner retinal layer thickness, which was in turn significantly associated with EZ recovery ( 22 ). A study by Sevgi et al showed that EZ-RPE thickness at 1-month follow-up in MH patients was significantly correlated with BCVA at 12 months postoperatively ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] This is followed by the gradual restoration of EZ with the prerequisite of an intact outer nuclear layer (ONL). [ 21 22 ] ELM is thought to be composed of Muller cells’ terminal processes which surround photoreceptor cells. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 10 ] However, very few studies are available on simultaneous microstructural analysis of all retinal layers and their remodeling influencing structural and functional outcomes. [ 11 ]…”
mentioning
confidence: 99%